Revealing Transitive Verbs in Arabic Short Stories: A Case of Tagmemic Approach - abdul basid; Al Lastu Nurul Fatim; Jumriyah Jumriyah; Masrokhin Masrokhin (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
The study aimed to reveal transitive verbs, both active and passive monotransitive, in the Arabic short story “al-’Ajuz was al-’Ushfur” by Mahasin Jadu by using Kenneth L. Pike’s tagmemic theory, which consists of four elements. This study was qualitative-descriptive. Data was collected by reading and noting techniques from short story texts based on Kenneth L. Pike’s four tagmemic elements. The result of the study showed that based on Kenneth L. Pike’s four tagmemic elements, active transitive verbs were expressed by using four structures: (1) transitive verb phrase, noun phrase 1, and noun phrase 2; (2) transitive verb phrase, noun phrase 1, noun phrase 2, and adjunct (prepositional phrase); (3) transitive verb phrase, noun phrase 1, and noun phrase 2; (4) transitive verb phrases (noun phrase 1), adjunct (prepositional phrase), and noun phrase 2. The passive monotransitive verbs founded on one structure were expressed by using transitive verb phrases, noun phrases 1, and noun phrases 2. The result of this study shows that in many cases of transitive phrases, both active and passive monotransitive forms might stimulate the notion of different meanings by using their own syntactic structures.